Spatial and temporal patterns of Zaire ebolavirus antibody prevalence in the possible reservoir bat species - X. Pourrut (2018)
To characterize the distribution of Zaire ebolavirus (ZEBOV) infection within the 3 bat species (Epomops franqueti, Hypsignathus monstrosus, and Myonycteris torquata) that are possible reservoirs, we collected 1390 bats during 2003-2006 in Gabon and the Republic of the Congo. Detection of ZEBOV immunoglobulin G (IgG) in 40 specimens supports the role of these bat species as the ZEBOV reservoirs. ZEBOV IgG prevalence rates (5%) were homogeneous across epidemic and nonepidemic regions during outbreaks, indicating that infected bats may well be present in nonepidemic regions of central Africa. ZEBOV IgG prevalence decreased, significantly, to 1% after the outbreaks, suggesting that the percentage of IgG-positive bats is associated with virus transmission to other animal species and outbreak appearance. The large number of ZEBOV IgG-positive adult bats and pregnant H. monstrosus females suggests virus transmission within bat populations through fighting and sexual contact. Our study, thus, helps to describe Ebola virus circulation in bats and offers some insight into the appearance of outbreaks. © 2007 by the Infectious Diseases Society of America. All rights reserved.